Genome-wide association analyses of agronomic traits and Striga hermonthica resistance in pearl millet - Rouamba, Armel; Shimelis Hussien; Drabo, Inoussa; Mrema, Emmanuel; Ojiewo, Christopher Ochieng; Mwadzingeni, Learnmore; Rathore, Abhishek (Nature Publishing Group, 2023)
Pearl millet (Pennisetum glaucum [L.] R. Br.) is a nutrient-dense, relatively drought-tolerant cereal crop cultivated in dry regions worldwide. The crop is under-researched, and its grain yield is low (< 0.8 tons ha−1) and stagnant in the major production regions, including Burkina Faso. The low productivity of pearl millet is mainly attributable to a lack of improved varieties, Striga hermonthica [Sh] infestation, downy mildew infection, and recurrent heat and drought stress. Developing high-yielding and Striga-resistant pearl millet varieties that satisfy the farmers’ and market needs requires the identification of yield-promoting genes linked to economic traits to facilitate marker-assisted selection and gene pyramiding. The objective of this study was to undertake genome-wide association analyses of agronomic traits and Sh resistance among 150 pearl millet genotypes to identify genetic markers for marker-assisted breeding and trait introgression. The pearl millet genotypes were phenotyped in Sh hotspot fields and screen house conditions. Twenty-nine million single nucleotide polymorphisms (SNPs) initially generated from 345 pearl millet genotypes were filtered, and 256 K SNPs were selected and used in the present study. Phenotypic data were collected on days to flowering, plant height, number of tillers, panicle length, panicle weight, thousand-grain weight, grain weight, number of emerged Striga and area under the Striga number progress curve (ASNPC). Agronomic and Sh parameters were subjected to combined analysis of variance, while genome-wide association analysis was performed on phenotypic and SNPs data. Significant differences (P < 0.001) were detected among the assessed pearl millet genotypes for Sh parameters and agronomic traits. Further, there were significant genotype by Sh interaction for the number of Sh and ASNPC. Twenty-eight SNPs were significantly associated with a low number of emerged Sh located on chromosomes 1, 2, 3, 4, 6, and 7. Four SNPs were associated with days-to-50%-flowering on chromosomes 3, 5, 6, and 7, while five were associated with panicle length on chromosomes 2, 3, and 4. Seven SNPs were linked to thousand-grain weight on chromosomes 2, 3, and 6. The putative SNP markers associated with a low number of emerged Sh and agronomic traits in the assessed genotypes are valuable genomic resources for accelerated breeding and variety deployment of pearl millet with Sh resistance and farmer- and market-preferred agronomic traits.